(untitled) (Research, Society and Development, 2021)
Avocado is a nutritious fruit of the species Persea americana Mill, this hybrid cultivar belongs to the Lauraceae botanical family and has its origin in the American continent, widely produced in the Brazilian territory. Although this fruit has a high nutritional value, little is known about its phytochemical nature and antioxidant properties. The objective of this research was to evaluate the levels of carotenoids and antioxidant activity in the ripe pulp of avocado (Persea americana Mill). The pulp of the fruit was extracted by maceration, the samples were analyzed according to the methodology described in the literature for total carotenoids, and antioxidant activity by the methods - ABTS, DPPH and FRAP. The quantification of phytochemical parameters was performed by means and standard deviations. And the statistical evaluation was determined through analysis of variance and comparison by the Tukey test with a significance level of p <0.05. The results indicate that the avocado pulp is rich in carotenoids, mainly α-carotene, canthaxanthin, β-cryptoxanthin, zeaxanthin, β-carotene and β-zeacarotene, whereas phytofluene appeared in a small amount (4.81 μg of β -carotene) in this part of the fruit. The bioactive compounds determined by DPPH showed results ranging from 41.10 to 98.32 µmolTrolox.g-1, and ABTS, which showed results ranging from 141, 54 µmolTrolox.g-1 to 402.14 µmolTrolox.g-1. Thus, the high content of carotenoids found, is a source of antioxidants that stabilize free radicals, important in combating oxidative stress.